Hospital frailty risk score in predicting outcomes after simultaneous colon and liver resection for colorectal cancer liver metastasis in older adults: Evidence from the Nationwide Inpatient Sample 2015–2018 - Haohao Huang; Weidong Jin; Huiling Sun; Bo Diao; Ping Wang; Jiankun Jia; Dandan Ma; Yi Zhang (The Journal of Nutrition, Health and Aging)
Objectives: This study investigated the impact of clinical frailty on short-term outcomes of simultaneous colorectal cancer (CRC) and colorectal cancer liver metastasis (CRLM) resections. Setting and participants: Data of older patients ≥ 60 years old undergoing simultaneous CRC/CRLM resections between 2005 and 2018 were identified in the United States (US) Nationwide Inpatient Sample (NIS) database. Methods: Frailty was determined using the Hospital Frailty Risk Score (HFRS) according to the International Classification of Diseases Ninth and Tenth (ICD-9 and ICD-10) codes. Study outcomes included mortality, prolonged hospital stay (LOS), non-routine discharge, and complications. Results: Data of 4514 patients were analyzed. Frailty was significantly associated with increased risks of in-hospital mortality (adjusted odds ratio [aOR] = 3.65, 95% confidence interval [CI]: 2.52, 5.28), non-routine discharge (aOR = 2.44, 95% CI: 2.08, 2.87), prolonged LOS (aOR = 3.07, 95% CI: 2.60, 3.61), overall complications (aOR = 3.47, 95% CI: 3.03, 3.97), sepsis (aOR = 13.73, 95% CI: 9.76, 19.31), respiratory failure (aOR = 4.99, 95% CI: 3.80, 6.57), acute kidney injury (AKI) (aOR = 6.42, 95% CI: 4.83, 8.52), and acute liver failure (aOR = 2.10, 95% CI: 1.38, 3.21), as well as 32.69 thousand USD higher total hospital costs (95% CI: 28.41, 36.97) than no frailty. Incorporating frailty with traditional demographic and clinical risk factors improved in-hospital mortality prediction (area under ROC curve [AUC]: 0.765 to 0.799). Conclusions: In older patients aged ≥ 60 years undergoing simultaneous CRC and CRLM resection, HFRS-defined frailty is a significant predictor of adverse in-hospital outcomes. The addition of HFRS-defined frailty to demographic and clinical variables in predictive models improved the AUC for mortality prediction. Incorporating frailty assessment into the preoperative risk stratification and decision-making process for these patients may support surgeons in delivering more personalized and effective care.